The emergence of male leadership in competitive environments - Ernesto Reuben; Pedro Rey-Biel; Paola Sapienza; Luigi Zingales (Institute for the Study of Labor (IZA), 2010)
We present evidence from an experiment in which groups select a leader to compete against the leaders of other groups in a real-effort task that they have all performed in the past. We find that women are selected much less often as leaders than is suggested by their individual past performance. We study three potential explanations for the underrepresentation of women, namely, gender differences in overconfidence concerning past performance, in the willingness to exaggerate past performance to the group, and in the reaction to monetary incentives. We find that men's overconfidence is the driving force behind the observed prevalence of male representation.
Keywords: J71; D03; C92; 330; discrimination; gender gap; glass ceiling; overconfidence; leadership; Führungskräfteauswahl; Männer; Arbeitsgruppe; Wettbewerb; Geschlechterdiskriminierung; Weibliche Führungskräfte; Test